Non coding RNAs as the critical factors in chemo resistance of bladder tumor cells - Amir Sadra Zangouei; Hamid Reza Rahimi; Majid Mojarrad; Meysam Moghbeli (BMC, 2020)
Abstract Background Bladder cancer (BCa) is the ninth frequent and 13th leading cause of cancer related deaths in the world which is mainly observed among men. There is a declining mortality rates in developed countries. Although, the majority of BCa patients present Non-Muscle-Invasive Bladder Cancer (NMIBC) tumors, only 30% of patients suffer from muscle invasion and distant metastases. Radical cystoprostatectomy, radiation, and chemotherapy have proven to be efficient in metastatic tumors. However, tumor relapse is observed in a noticeable ratio of patients following the chemotherapeutic treatment. Non-coding RNAs (ncRNAs) are important factors during tumor progression and chemo resistance which can be used as diagnostic and prognostic biomarkers of BCa. Main body In present review we summarized all of the lncRNAs and miRNAs associated with chemotherapeutic resistance in bladder tumor cells. Conclusions This review paves the way of introducing a prognostic panel of ncRNAs for the BCa patients which can be useful to select a proper drug based on the lncRNA profiles of patients to reduce the cytotoxic effects of chemotherapy in such patients.